Harmfulness of beet nematode in table and fodder beet crops - Kalatur, К. (Quarantine and plant protection, 2025)
Goal. To determine the degree of harmfulness of the beet cyst nematode (Heterodera schachtii Schmidt) in table (Beta vulgaris L. var. conditiva) and fodder (Beta vulgaris L. var. crassa) beet crops; to analyze its impact on the morphophysiological state of plants and crop productivity; to identify the factors influencing the population dynamics of this parasite in the soil; and to substantiate an effective system for protecting crops from H. schachtii infestation, taking into account modern phytosanitary requirements. Methods. Laboratory-field and statistical methods were used. The research was conducted during 2021—2023 in Kyiv region, where small-plot experiments were established under natural infestation conditions. To determine the abundance of the beet cyst nematode in the soil, samples were collected and analyzed before sowing, after the development of the first generation of the parasite, and before harvesting the beets. In laboratory conditions, cysts of H. schachtii were extracted from 100 cm³ of soil using the flotation-funnel method, and the number of eggs and larvae inside them was counted. Results. It was established that under favorable weather conditions (primarily air temperature), cultivation of table and fodder beet crops as host plants on nematode-infested fields promotes the development of three parasite generations during the growing season and increases its population density by 105.6—254.1 times. The increase in the harmfulness of H. schachtii in these crops led to a significant reduction in root crop weight (by 60—80%), and in some cases — to complete yield loss. Conclusions. The research results demonstrated that cultivation of table or fodder beet on fields infested with beet nematode promotes the intensive reproduction of this parasite throughout the growing season and increases its population density in the soil, especially under favorable meteorological conditions. It was scientifically substantiated that reducing the number and harmfulness of H. schachtii to an economically insignificant level is possible only through the implementation of an integrated approach that combines organizational (systematic nematological field monitoring), agrotechnical, and biological protection measures, taking into account current climate change.